2006
DOI: 10.1007/s00011-006-5088-0
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ inhibits collagen phagocytosis in human fibroblasts by inducing subcortical actin assembly and reducing ability of β1 integrin to bind to collagen

Abstract: Although IFN-gamma does not appreciably moderate the extracellular route of collagen digestion by human fibroblasts, the reduced level of collagen phagocytosis by IFN-gamma in the cells may contribute to fibrosis in inflamed connective tissues. Further, IFN-gamma may decrease the binding of collagen and following phagocytosis in cells by inducing a subcortical actin assembly and reducing the ability of beta1 integrin to bind to collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Previously, Tabe et al indicated that ILK/Akt are involved in a proximal signaling pathway critical for the survival of leukemic cells within the BM microenvironment (10). Moreover, it has also been reported that exposure of human fibroblasts to IFN-γ induces a subcortical actin assembly and subsequently reduces the affinity activity of β1 integrin during its engagement with collagen (11). These results have revealed that there may be a correlation between IFN-γ and β1 integrin.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Tabe et al indicated that ILK/Akt are involved in a proximal signaling pathway critical for the survival of leukemic cells within the BM microenvironment (10). Moreover, it has also been reported that exposure of human fibroblasts to IFN-γ induces a subcortical actin assembly and subsequently reduces the affinity activity of β1 integrin during its engagement with collagen (11). These results have revealed that there may be a correlation between IFN-γ and β1 integrin.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the intracellular collagen degradation is prevalent in connective tissues with a rapid turnover of collagen, including gingival tissue (21). Furthermore, inflammatory cytokines such as tumor necrosis factor‐α and interferon‐γ decrease collagen phagocytosis by gingival fibroblasts (5, 27), suggesting that the inhibition by these inflammatory cytokines of fibroblast collagen phagocytosis contributes to collagen overgrowth in inflamed gingival tissue. However, little is known about the regulatory effect of LPS from periodontopathogens on collagen phagocytosis by fibroblasts and the associated regulatory mechanisms.…”
mentioning
confidence: 99%
“…Typical HGF populations isolated from the tissues of each of the three volunteers were designated as HGF‐1, ‐2, and ‐3. Collagen phagocytic activity in HGF was determined using an assay for internalization of collagen‐coated beads, following the previously published method (27). Similar to the findings of previous studies (5, 27), when HGF were incubated with collagen‐coated beads for 3 h in medium with 0.5% bovine serum albumin (BSA), the percentage of cells that contained ingested beads was increased (mean 22.3%) (data not shown).…”
mentioning
confidence: 99%
See 1 more Smart Citation